2015
DOI: 10.5507/bp.2015.009
|View full text |Cite
|
Sign up to set email alerts
|

CT-1 induces angiogenesis by regulating the ADMA/DDAH Pathway

Abstract: Background. Cardiotrophin-1 (CT-1), a member of the IL-6 superfamily, is elevated in the serum of patients with ischemic and valvular heart disease. In this study, we hypothesized that CT-1 induces endothelial cell angiogenesis and that the ADMA/DDAH pathway plays an important role in the process. Methods. pEGFP-N1-CTF1-GFP and pEGFP-N1 were constructed and used to transiently transfect to HUVECs, mediated by LipofectamineTM 2000. After transfection, the expression of CT-1 was examined by qRT-PCR and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…CT-1 is a member belonging to IL-6 superfamily (35). By interacting with the heterodimer comp osed of glycoprotein 130 and leukemia inhibitory factor receptor-β, this cytokine exerts a series of cellular effects (36).…”
Section: Discussionmentioning
confidence: 99%
“…CT-1 is a member belonging to IL-6 superfamily (35). By interacting with the heterodimer comp osed of glycoprotein 130 and leukemia inhibitory factor receptor-β, this cytokine exerts a series of cellular effects (36).…”
Section: Discussionmentioning
confidence: 99%
“…CTF1 has been identified as an important regulator of cardiac, renal, hepatic, and nervous system functionality that has also recently been detected in the murine endometrium during the early stages of pregnancy ( Kobayashi et al, 2014 ). At a functional level, this cytokine is known to promote endothelial cell and neuronal survival, proliferation, migration, and differentiation, and it can also promote MSC persistence following injection into a particular tissue site ( Zheng et al, 2015 ; Bortolotti et al, 2017 ). Yang et al (2008) determined that CTF1 treatment was linked to transient increases in microvessel density and VEGF production, suggesting that these two cytokines influence one another to drive angiogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al determined that CTF1 was able to enhance tissue regeneration in the context of liver cirrhosis by promoting cellular proliferation and angiogenesis ( Yang et al, 2008 ), consistent with evidence that CTF1 overexpression using an adenoviral vector can improve liver function and survival associated with small-for-size grafts ( Song et al, 2008 ). Such CTF1 expression has been shown to drive the proliferative, migratory, and angiogenic activity of endothelial cells via the ADMA/DDAH pathway ( Zheng et al, 2015 ). Kobayashi et al (2014) further employed an in vivo functional screening approach that identified CTF1 as an important promoter of successful embryo implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The direct atherogenic effects of CT-1 on vascular wall cells are shown in Figure 3. CT-1 stimulates the migration and proliferation of human umbilical vein ECs [64], which contributes to atherogenesis as well as angiogenesis. CT-1 stimulates the synthesis of inflammatory cytokines and proatherogenic molecules, such as IL-6, monocyte chemoattractant protein-1, intercellular adhesion molecule-1, and MMP-1, in human ECs [26,[65][66][67].…”
Section: Atheroprone Effects Of Ct-1mentioning
confidence: 99%